Biomimetic scaffold based on ptcu nanowire-nsi-mineralized collagen fiber and preparation method thereof

CN120346372BActive Publication Date: 2026-10-30HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510295836.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2026-10-30
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

然而,传统的骨替代品在重建骨的电环境方面存在困难

Benefits of technology

[0020]有益效果:与现有技术相比,本发明具有以下显著优点:本发明将PtCu纳米线、nSi与矿化胶原纤维共同构筑具有稳定电刺激和快速清除ROS功能的自供电仿生导电支架,该仿生支架中的纤维径向排列可以模拟天然骨组织结构,有利于细胞迁移和营养成分传输;仿生支架中的nSi在生理环境下水解释放出硅酸离子和氢气(H2),发生原电池反应,H2可干扰细菌代谢活动,诱发细菌凋亡,并通过清除炎症区域的•OH自由基缓解炎症。同时,支架中负载的PtCu纳米线基于其固有的抗氧化纳米结构,可以加速ROS清除水平,实现对感染性骨缺损部位多余自由基的快速清除。此外,PtCu纳米线作为良导体,可以加速nSi水解进程传递微电流至骨损伤部位,进一步加速骨修复进度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120346372B_ABST
    Figure CN120346372B_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on PtCu nanowire-nSi-mineralized collagen fiber biomimetic scaffold and its preparation method, the above biomimetic scaffold is with mineralized collagen fiber as scaffold main body, PtCu nanowire and nSi are deposited on mineralized collagen fiber together.The radial arrangement of mineralized collagen fiber in the application can simulate the structure of natural bone tissue, which is beneficial to cell migration and nutrient transport.nSi produces hydrogen gas under physiological conditions to eliminate ·OH free radicals, relieve inflammation, and the excess hydrogen is used for antibacterial and anti-infection.PtCu nanowire, as an excellent conductor, can timely export electrons, accelerate the nSi hydrolysis process, and at the same time, the micro-current generated during the redox process is transmitted to the bone injury site to promote bone tissue repair.PtCu nanowire itself also has ROS scavenging ability, which can accelerate the elimination of inflammation.The preparation process of the application is simple, safe and controllable, and has potential application prospects in the field of biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fibers and its preparation method. Background Technology

[0002] While human bone tissue possesses a natural self-healing capacity, reconstructing large bone defects exceeding this capacity presents a significant challenge in clinical practice. Large bone defects typically require suitable bone substitutes, such as autologous or allogeneic grafts, to support repair and regeneration. Autologous grafts are the gold standard for treating large bone defects, but their availability is limited due to donor site damage, while allogeneic grafts are associated with risks of contamination, disease transmission, and graft rejection. Therefore, designing biomimetic scaffolds based on biomaterials to guide host repair cells to aggregate at the injury site and promote in situ osteoogenesis is an effective alternative strategy to overcome the limitations of autologous and allogeneic transplantation.

[0003] Following scaffold implantation, the bone healing process is often disrupted by excessive acute inflammation, leading to elevated levels of reactive oxygen species (ROS) and prolonged healing time. Among the excessively produced ROS, hydroxyl radicals (•OH) are the most cytotoxic, reacting with biomolecules such as proteins, lipids, and nucleic acids, causing extensive damage to host repair cells and inhibiting their osteogenic differentiation. Conversely, some ROS, such as superoxide anions (•O2), can also promote bone healing. − Antioxidants play a crucial biological role in the control signal transduction cascade and possess beneficial physiological functions. Studies have shown that some antioxidants, such as vitamin C, vitamin E, salicylic acid, and curcumin, can alleviate the harmful effects of ROS at disease sites. However, common antioxidant components cannot distinguish between •OH, which causes cellular oxidative stress, and biologically active •O2. − This can easily trigger various adverse reactions (Biomaterials, 2022, 286:121574). Therefore, it is of great significance to design scaffolds with efficient and targeted ROS removal capabilities while retaining bioactive functions, and to develop novel materials that can construct a bone repair microenvironment at bone defect sites.

[0004] In recent years, hydrogen (H2) therapy has received widespread attention due to its high efficacy and good biocompatibility. Multiple studies have demonstrated that H2 can selectively reduce •OH in living cells, and inhalation of H2 gas can significantly reduce oxidative stress and inhibit cerebral ischemia-reperfusion injury. Furthermore, H2 can highly penetrate biological membranes and diffuse into the cytoplasm, organelles, and nucleus. It also has a high level of biocompatibility with few side effects on humans. In recent years, H2 has been widely used as an antioxidant to treat ROS overexpression-related diseases, including ischemic injury, cancer, stroke, arthritis, dermatitis, and Parkinson's disease (Nature Medicine, 2007, 13(6): 688-694).

[0005] Infected bone defects are considered a serious challenge in orthopedics due to their high treatment failure rate. Bacterial infection severely hinders the bone regeneration process. Once a bacterial biofilm forms, it repeatedly stimulates the infected tissue in the lesion, leading to inflammatory bone hyperplasia and ischemic necrosis of new bone, thereby greatly inhibiting the bone healing process. To date, combined antibiotic therapy is a common strategy for the clinical treatment of infected bone defects. However, antibiotics are difficult to treat complex infections caused by drug-resistant bacteria. More seriously, antibiotics also inhibit the osteoinductive properties of bone grafts by disrupting the balance of the human microbiome ecosystem, ultimately leading to a "double failure" of both anti-infection and bone repair. This dilemma urgently requires the development of new bone tissue engineering technologies to balance antibacterial and osteoinductive properties.

[0006] The piezoelectricity of natural bone has been recognized as an important factor in maintaining bone physiological function. Natural bone tissue possesses an endogenous electroactive interface that can induce stem cell differentiation and inhibit bacterial adhesion and activity. Bone tissue can spontaneously generate endogenous electrical signals due to the polarization of collagen fibrils caused by shear stress. These weak electrical signals play a decisive role in stem cell differentiation and tissue regeneration. Furthermore, electrical stimulation has been shown to promote osteoblast attachment and proliferation while inhibiting bacterial activity (ACS Catalysis, 2022, 12(6): 3604-3614). However, traditional bone substitutes face difficulties in reconstructing the electrical environment of bone. Therefore, developing bone tissue engineering scaffolds that can mimic the electroactive microenvironment of natural bone is of great significance for the effective treatment of infected bone defects. Summary of the Invention

[0007] Purpose of the invention: The first purpose of this invention is to provide a biomimetic scaffold based on PtCu nanowire-nSi-mineralized collagen fibers that can simulate the natural bone electroactive microenvironment and has excellent bone repair capabilities. The second purpose of this invention is to provide a method for preparing the above-mentioned biomimetic scaffold based on PtCu nanowire-nSi-mineralized collagen fibers.

[0008] Technical solution: The biomimetic scaffold based on PtCu nanowires-nSi-collagen fibers provided by the present invention uses mineralized collagen fibers as the main body of the scaffold, and PtCu nanowires and nSi are co-deposited on the mineralized collagen fibers.

[0009] Furthermore, the biomimetic scaffold has a porous structure with a pore size of 5-500 μm; the PtCu nanowires have a diameter of 20-200 nm; and the nSi has a size of 10-100 nm.

[0010] The aforementioned biomimetic scaffold's substrate is constructed from mineralized collagen fibers (MC). The radial arrangement of the MC fibers mimics the structure of natural bone tissue, facilitating cell migration and nutrient transport. nSi can hydrolyze under physiological conditions, producing hydrogen gas to eliminate •OH free radicals, alleviating inflammation. Excess hydrogen can also be used for antibacterial and anti-infective purposes. PtCu nanowires, as excellent conductors, can readily extract electrons, accelerating the nSi hydrolysis process. Simultaneously, the microcurrent generated during this redox process is transmitted to the bone injury site, promoting bone tissue repair. Furthermore, PtCu nanowires themselves possess ROS scavenging capabilities, which can accelerate inflammation reduction and enhance the electrostimulation effect on bone repair.

[0011] This invention provides a method for preparing the above-mentioned biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fibers, comprising the following steps: (1) Add solid collagen fibers to a solvent, add glacial acetic acid, stir evenly, adjust the pH to 9.0±0.5 to obtain collagen gel slurry; mix the obtained collagen gel slurry with calcium chloride solution with pH 9.0±0.5 and ammonium phosphate solution with pH 9.0±0.5, stir, filter and wash the obtained slurry, and redisperse the obtained product in a solvent to obtain mineralized collagen fiber solution; (2) Platinum salt and copper salt, surfactant, solvent, ethylene glycol and N,N-dimethylformamide are mixed and stirred to form a uniform reaction solution, and then hydrothermal reaction is carried out. After the reaction is completed, the product is washed and centrifuged. The product is suspended in acid solution for heat treatment. After the reaction is completed, the product is washed, centrifuged and dried to obtain Pt-Cu nanowires. (3) Add nSi to the solvent and disperse by ultrasonication to obtain a uniform amorphous nano-silicon suspension: (4) Mix mineralized collagen fiber solution, PtCu nanowires and amorphous nano-silicon suspension, stir evenly and then freeze. After the freeze treatment, a biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fiber is obtained.

[0012] Further, in step (1), the ratio of the solid collagen fiber, solvent and glacial acetic acid is 0.1-0.2g:20-40 mL:30-60 μL; the mass concentration of the calcium chloride solution is 0.02-0.09 g / mL; and the mass concentration of the ammonium phosphate solution is 0.03-0.12 g / mL.

[0013] Further, in step (1), the volume ratio of the collagen gel paste, calcium chloride solution and ammonium phosphate solution is 20-30:1-3:1-3; the mass concentration of the mineralized collagen fiber is 0.002-0.12 g / mL, preferably 0.003-0.006 g / mL.

[0014] Further, in step (2), the molar ratio of the platinum salt to the copper salt is 3:1 to 1:2, preferably 1:1. By reasonably controlling the molar ratio of the platinum salt to the copper salt, the synergistic effect of the conductivity and ROS scavenging function of the PtCu nanowires can be optimized to achieve the best therapeutic purpose. The platinum salt is chloroplatinic acid hexahydrate, the copper salt is copper chloride dihydrate, and the surfactant is sodium dodecyl sulfate. The molar ratio of the copper salt to the surfactant is 1:1-2. The volume ratio of the solvent, ethylene glycerol, and N-dimethylformamide is 5-20:1-2:1-2.

[0015] Further, in step (2), the parameters of the hydrothermal reaction are: reacting at 160-180℃ for 6-8 h; the acid solution is acetic acid, and the heat treatment conditions are: heating at 60-70℃ for 8-24 h; the parameters of the centrifugation are: rotation speed of 8000-9000 rpm and centrifugation time of 5-10 min; the parameters of the drying are: drying at 60-70℃ for 6-8 h.

[0016] Further, in step (3), the mass concentration of the amorphous nano-silicon suspension is 0.005-0.008 g / mL.

[0017] Further, in step (4), the ratio of the amount of mineralized collagen fiber solution, PtCu nanowires, and amorphous nano-silicon suspension is 5-60 mL: 5-60 mg: 0.1-3 mL, preferably 25-50 mL: 5-25 mg: 1-2 mL. When the mass concentration of mineralized collagen fiber is 0.003 g / mL and the mass concentration of amorphous nano-silicon suspension is 0.005 g / mL, the mass ratio of mineralized collagen fiber, PtCu nanowires, and nSi is 75-150: 5-25: 5-10.

[0018] Furthermore, in step (4), the time for stirring evenly is 2-4 h; the time for freezing treatment is 24-72 h.

[0019] Furthermore, in steps (1) to (4), the solvent is water.

[0020] Beneficial Effects: Compared with existing technologies, this invention has the following significant advantages: This invention constructs a self-powered biomimetic conductive scaffold with stable electrical stimulation and rapid ROS scavenging functions using PtCu nanowires, nSi, and mineralized collagen fibers. The radial arrangement of fibers in this biomimetic scaffold can simulate the structure of natural bone tissue, which is beneficial for cell migration and nutrient transport. Under physiological conditions, the nSi in the biomimetic scaffold hydrolyzes, releasing silicate ions and hydrogen (H2), resulting in a galvanic cell reaction. H2 can interfere with bacterial metabolic activities, induce bacterial apoptosis, and alleviate inflammation by scavenging •OH free radicals in the inflammatory area. Simultaneously, the PtCu nanowires loaded in the scaffold, based on their inherent antioxidant nanostructure, can accelerate ROS scavenging levels, achieving rapid removal of excess free radicals from infected bone defects. Furthermore, as good conductors, PtCu nanowires can accelerate the nSi hydrolysis process, delivering microcurrents to the bone injury site, further accelerating bone repair. Attached Figure Description

[0021] Figure 1 This is a general morphological diagram of the PtCu-nSi-MC (bionic scaffold) prepared in Example 1; Figure 2 Scanning electron microscope image of the PtCu-nSi-MC (bionic scaffold) prepared in Example 1; Figure 3 Surface microcurrent curves of MC and PtCu-nSi-MC in PBS buffer; Figure 4 For each group of samples, the effects of •OH and •O2 are as follows: − Clear the horizontal histogram; Figure 5 The bar chart shows the relative cell viability of osteoblasts after co-culturing with each group of samples. Figure 6 The image shows the fluorescence of osteoblasts after co-culturing with each group of samples. Detailed Implementation

[0022] The present invention will now be further described in conjunction with specific embodiments and accompanying drawings.

[0023] Example 1: The biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fibers provided in this example uses mineralized collagen fibers as the main body of the scaffold, with PtCu nanowires and nSi co-deposited on the mineralized collagen fibers. The preparation method is as follows: (1) 0.1 g of solid collagen fibers were added to 20 mL of deionized water, and 30 μL of glacial acetic acid were added. The mixture was stirred to form a homogeneous gel. 0.165 g of calcium chloride was dissolved in 3 mL of deionized water to prepare a calcium chloride solution. 0.129 g of (NH4)2HPO4 (ammonium phosphate dialkali) was added to 3 mL of deionized water to obtain an ammonium phosphate solution. The pH of each prepared solution (gel, calcium chloride solution, and ammonium phosphate solution) was adjusted to approximately 9.0 by adding ammonium hydroxide. The solutions were then mixed together and stirred at room temperature for 15 min. After standing for 1 h, the resulting MC slurry was filtered through filter paper, washed with deionized water, and then dispersed in deionized water to obtain a mineralized collagen fiber solution with a mass concentration of 0.003 g / mL for later use.

[0024] (2) 5 mL of 0.01 M H₂PtCl₆-6H₂O (chloroplatinic acid hexahydrate), 5 mL of 0.01 M CuCl₂-2H₂O (copper chloride dihydrate), 5 mL of 0.1 M SDS (sodium dodecyl sulfate), 5 mL of H₂O, 1 mL of EG (ethylene glycol), and 1 mL of DMF (N,N-dimethylformamide) were mixed in a 50 mL vial. The vial was capped and stirred at room temperature for 4 hours. The solution was then transferred to a 50 mL reaction vessel and heated at 180 °C for 8 h. After cooling to room temperature, the product was washed with ethanol and water, centrifuged at 8000 rpm for 5 min, and then suspended in 6 mL of acetic acid and heated overnight in a 70 °C oven. The product treated with acetic acid was centrifuged, washed with ethanol, and then dried in a 60 °C vacuum oven for 8 h to obtain PtCu nanowires.

[0025] (3) Add nSi powder to deionized water and ultrasonically disperse it evenly to prepare an aqueous suspension of nSi with a mass concentration of 0.005 g / mL.

[0026] (4) The prepared PtCu nanowires, mineralized collagen fiber solution, and nSi aqueous suspension were mixed (the ratio of PtCu nanowires, mineralized collagen fiber solution, and nSi aqueous suspension was 10 mg:25 mL:1 mL), stirred evenly, and then frozen in a refrigerator for 24 h. After that, it was dried in a freeze dryer to obtain the final sample PtCu-nSi-MC (bionic scaffold). The actual object is shown in the figure below. Figure 1 As shown.

[0027] The microstructure of the PtCu-nSi-MC prepared in Example 1 was characterized, and the results are shown in the figure. Figure 2 .like Figure 2As shown, PtCu-nSi-MC was assembled into a micron-sized three-dimensional porous implantable scaffold material with high porosity, with a pore size of approximately 50 µm, using a freeze-drying method. The biomimetic bone structure morphology with high specific surface area of ​​this scaffold material plays a positive role in promoting the recruitment of osteoblast stem cells and subsequent cell proliferation and differentiation.

[0028] Example 2: The difference from Example 1 is that in step (4), the ratio of PtCu nanowires, collagen fiber solution and nSi aqueous suspension is 7.5 mg: 25 mL: 1.5 mL.

[0029] Example 3: The difference from Example 1 is that in step (4), the ratio of PtCu nanowires, collagen fiber solution and nSi aqueous suspension is 5 mg: 25 mL: 2 mL.

[0030] Comparative Example 1: The MC stent provided in this comparative example is prepared by the following method: (1) Prepare a mineralized collagen fiber solution with a mass concentration of 0.003 g / mL, using the same method as in Example 1; (2) After freezing the above mineralized collagen fiber solution in a refrigerator for 24 hours, it was then dried in a freeze dryer to obtain the MC scaffold.

[0031] Comparative Example 2: The PtCu-MC scaffold provided in this comparative example is prepared by the following method: (1) Prepare a mineralized collagen fiber solution with a mass concentration of 0.003 g / mL, using the same method as in Example 1; (2) PtCu nanowires were prepared using the same method as in Example 1; (3) Mix 10 mg of PtCu nanowires with 25 mL of mineralized collagen fiber solution, stir evenly, freeze in a refrigerator for 24 h, and then dry in a freeze dryer to obtain the final sample PtCu-MC.

[0032] Comparative Example 3: The nSi-MC scaffold provided in this comparative example is prepared by the following method: (1) Prepare a collagen fiber solution with a mass concentration of 0.003 g / mL, using the same method as in Example 1; (2) Prepare an aqueous suspension of nSi with a mass concentration of 0.005 g / mL, using the same method as in Example 1; (3) Mix 1 mL of aqueous suspension of nSi and 25 mL of collagen fiber solution, stir evenly, freeze in a refrigerator for 24 h, and then dry in a freeze dryer to obtain the final sample nSi-MC.

[0033] The properties of the materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested: 1. Electrochemical testing: Electrochemical tests were performed using a typical three-electrode setup. PBS (pH 7.2–7.4) was used as the electrolyte. Electroactive scaffold-supported ITO glass electrodes, pure ITO glass electrodes, and Ag / AgCl electrodes (3.0 M potassium chloride) were used as the working electrode, counter electrode, and reference electrode, respectively. All samples, including those from Examples 1, 2, 3, and Comparative Example 1, were directly coated onto a 1.5 × 2 cm² plate. 2 ITO glass is used as the working electrode.

[0034] The obtained electrodes were mineralized at room temperature for 5-7 days, and thin films were obtained for further measurements. Details of the working electrode preparation are as follows: MC-loaded ITO, 150 μL collagen, 150 μL acetic acid, and 300 μL potassium phosphate buffer were uniformly assembled on an ITO glass as the MC. For PtCu-nSi-MC-loaded ITO, an aqueous solution of PtCu-nSi (10 mg / mL, 25 μL) was added to the above mineralized collagen fiber mixture and co-assembled on an ITO glass.

[0035] Finally, the ITO glass loaded with the sample was placed in a vacuum drying oven and mineralized for 5 days for subsequent electrochemical measurements.

[0036] Figure 3 The surface microcurrent curves of all samples in PBS buffer are provided. Compared to Comparative Example 1, Examples 1, 2, and 3 exhibit long-lasting and stable current output, with current intensities of ~3.9 μA, ~3.4 μA, and ~3.0 μA, respectively. Among them, Example 1 shows the best current output. The above experimental results demonstrate that the optimal current intensity is achieved when the mass ratio of PtCu nanowires:mineralized collagen fibers:nSi is 2 mg:15 mg:1 mg.

[0037] 2. Test to remove ROS: Two representative ROS, •OH and •O2, were selected. − The ROS scavenging ability of each sample (Examples 1, 2, and 3, and Comparative Examples 1, 2, and 3) was evaluated. The test scaffolds were immersed in 50 μL of PBS at 37°C for 12 h to obtain H2 solutions, which were immediately used to study their ROS scavenging ability. •OH scavenging activity was determined using the OxiSelect™ HORAC activity assay kit, and •O2 scavenging activity was determined using the SOD activity assay kit. − Eliminate activity.

[0038] Figure 4For each sample (Example 1, Example 2, Example 3, and Comparative Examples 1, 2, and 3), the effects of •OH and •O2 were respectively determined. − Clear the horizontal histogram. For example... Figure 4 As shown in (a), Examples 1, 2, 3, Comparative Example 2, and Comparative Example 3 all exhibit significant scavenging ability for •OH, with Example 1 showing the best scavenging ability for •OH, achieving a scavenging rate of ~60%. Figure 4 As shown in (b), Examples 1, 2, 3, and Comparative Example 2 exhibited weak scavenging abilities, with scavenging rates less than 30%. The above data demonstrate that the scaffold material possesses selective and rapid scavenging ability against cytotoxic •OH, with Example 1 showing the best ROS scavenging effect. The above experimental results demonstrate that the optimal ROS scavenging level is achieved when the mass ratio of PtCu nanowires:mineralized collagen fibers:nSi is 2 mg:15 mg:1 mg.

[0039] 3. Assay to promote osteoblast proliferation: To evaluate the effect of PtCu-nSi-MC electrostimulation on osteoblast proliferation, MC3T3-E1 cells were seeded at an appropriate density in 96-well plates, with 100 μL per well. Cells were incubated at 37°C with 5% CO2 until adherence. Samples (MC, PtCu-MC, nSi-MC, PtCu-nSi-MC) were then added to the wells. Cells were further incubated at 37°C with 5% CO2 for a period of time. Relative cell viability was determined using a CCK-8 cell viability assay kit.

[0040] Figure 5 The bar chart shows the relative cell viability of osteoblasts after co-culturing with each sample (Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 1). The data show that Example 1, Comparative Example 2, and Comparative Example 3 all have the ability to promote osteoblast proliferation. Among them, Example 1 exhibits a very significant osteoblast proliferation-promoting performance, with a growth rate of ~230%. Its excellent osteoblast proliferation-promoting ability is mainly attributed to the synergistic effect of •OH scavenging and electrostimulation by PtCu-nSi-MC. In comparison, Comparative Example 2, which does not contain nSi, has an osteoblast proliferation-promoting efficiency of ~145%, while Comparative Example 3, which does not contain PtCu nanowires, has an osteoblast proliferation-promoting efficiency of ~130%.

[0041] Figure 6 The images show fluorescence spectra of osteoblasts co-cultured with each group of samples (Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 1). These images are consistent with the cell viability histogram data, demonstrating that Example 1 exhibits excellent osteoblast proliferation-promoting ability. In contrast, Comparative Examples 2 and 3, lacking nSi or PtCu doping, showed poorer osteoblast proliferation-promoting effects.

[0042] 4. Antibacterial test: For the antibacterial experiment, *Escherichia coli* and *Staphylococcus aureus* were used as the experimental strains. The revived bacteria were placed in liquid culture medium and shaken overnight on a 37°C constant-temperature shaker. Samples from Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 1 were placed in 12-well plates, and 100 µL of bacterial suspension was added dropwise to the sample surface for each.

[0043] Add 1 mL of PBS solution to each sample group, sonicate, then take 50 μL of bacterial culture, plate it, place it on a 37℃ constant temperature shaker overnight, and observe the number of bacterial colonies.

[0044] Table 1. Bacterial survival rate results obtained in Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 1 of the present invention.

[0045] The statistical data of plate colonies in the in vitro antibacterial experiment are shown in Table 1 above. The results show that Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 1 all exhibited effective antibacterial effects against Escherichia coli and Staphylococcus aureus, and PtCu-nSi-MC showed the most significant antibacterial efficiency.

Claims

1. A biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fibers, characterized in that, Using mineralized collagen fibers as the main scaffold, PtCu nanowires and nSi are co-deposited on the mineralized collagen fibers; the preparation method of the biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fibers includes the following steps: (1) Add solid collagen fibers to a solvent, add glacial acetic acid, stir until homogeneous, and adjust the pH to 9.0±0.5 to obtain collagen gel slurry; mix the obtained collagen gel slurry with calcium chloride solution and ammonium phosphate solution at pH 9.0±0.5, stir, filter and wash the obtained slurry, and redisperse the obtained product in a solvent to obtain mineralized collagen fiber solution; the mass concentration of the mineralized collagen fiber solution is 0.002-0.12 g / mL; (2) Platinum salt and copper salt, surfactant, solvent, ethylene glycol and N,N-dimethylformamide are mixed and stirred to form a uniform reaction solution, and then hydrothermal reaction is carried out. After the reaction is completed, the product is washed and centrifuged. The product is suspended in acid solution for heat treatment. After the reaction is completed, the product is washed, centrifuged and dried to obtain PtCu nanowires. The molar ratio of platinum salt to copper salt is 3:1 to 1:

2. (3) Add nSi to the solvent and disperse it by ultrasonication to obtain a uniform amorphous nano-silicon suspension: the mass concentration of the amorphous nano-silicon suspension is 0.005-0.008 g / mL; (4) Mix mineralized collagen fiber solution, PtCu nanowires and amorphous nano-silicon suspension, stir evenly and then freeze. After freezing, a biomimetic scaffold based on PtCu nanowires-nSi-mineralized collagen fiber is obtained. The ratio of the amount of mineralized collagen fiber solution, PtCu nanowires and amorphous nano-silicon suspension is 5-60 mL: 5 mg-60 mg: 0.1-3 mL.

2. The bionic scaffold according to claim 1, characterized in that, The biomimetic scaffold has a porous structure with a pore size of 5-500 μm; the PtCu nanowires have a diameter of 20-200 nm; and the nSi has a size of 10-100 nm.

3. The bionic scaffold according to claim 1, characterized in that, In step (1), the ratio of the solid collagen fiber, solvent and glacial acetic acid is 0.1-0.2 g: 20-40 mL: 30-60 μL; the mass concentration of the calcium chloride solution is 0.02-0.09 g / mL; and the mass concentration of the ammonium phosphate solution is 0.03-0.12 g / mL.

4. The bionic scaffold according to claim 1, characterized in that, In step (1), the volume ratio of the collagen gel paste, calcium chloride solution and ammonium phosphate solution is 20-30:1-3:1-3.

5. The bionic scaffold according to claim 1, characterized in that, In step (2), the platinum salt is chloroplatinic acid hexahydrate and the copper salt is copper chloride dihydrate.

6. The bionic scaffold according to claim 1, characterized in that, In step (2), the parameters of the hydrothermal reaction are: reacting at 160-180℃ for 6-8 h; the acid solution is acetic acid, and the heat treatment conditions are: heating at 60-70℃ for 8-24 h.

7. The bionic scaffold according to claim 1, characterized in that, In step (4), the freezing process takes 24-72 hours.